Skills, training, and activism. Issue 4 (4th July 2017) - Martin, Brian; Coy, Patrick G.
Abstract: Most studies of activism and social movements give more attention to methods and strategies than to the development of skills. Yet skills are crucially important to the success of campaigns. Research on expert performance provides insights into what is required to become highly proficient at a well-defined set of skills. These insights are potentially relevant to activists, as shown by the example of training for lunch-counter sit-ins in Nashville, Tennessee in 1960. Skill development needs to be given greater attention by activists and scholars.